Habit and addiction in the use of social networking sites: Their nature, antecedents, and consequences. (October 2019) - Seo, DongBack; Ray, Soumya
Abstract: Habit and addiction are two distinct drivers of information technology (IT) use that nonetheless bear increasing resemblance in how they are conceptualized and modeled in the information systems (IS) literature. The purpose of this study is to aid the further growth of these heretofore-independent streams of research by developing a comparative framework that allows us to distinguish between them. Drawing on the theories of automaticity and incentive-sensitization, we developed a theoretical model that describes the nature, antecedents, and consequences of habit and addiction of IT use in the context of social networking services. The proposed model was tested based on the data collected from 420 actual users of Twitter. We found that habit was indeed influenced by its proposed unique antecedents of routine seeking and cognitive rigidity, whereas addiction was not. Similarly, addiction was influenced by its proposed unique antecedents of focused immersion and concern for social acceptance, whereas habit was not. Looking at their outcomes, we found that although both drivers positively affected goal-congruent outcomes, only habit enhanced goal-congruent usage and addiction had a negative impact. Overall, this study contributes to the IS literature by offering a robust conceptual framework that allows us to observe the profound differences between these superficially similar drivers of routine IT use. Highlights: Providing a unified framework that contrasts habit and addiction in the context of SNS use. Suggesting several distinct antecedent mechanisms that compare SNS habit and addiction. Examining the different outcomes and consequences of SNS habit and addiction. The findings can be used for the design and management of online services.